1998
DOI: 10.1073/pnas.95.14.8262
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ɛ protein kinase C correlates with a cardioprotective effect of regular ethanol consumption

Abstract: Medical Sciences. In the article "Activation of protein kinase C correlates with a cardioprotective effect of regular ethanol consumption" by Masami Miyamae, Manuel M. Rodriguez, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
15

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 60 publications
(86 reference statements)
6
84
1
15
Order By: Relevance
“…Chronic EtOH exposure (48 h) promotes translocation of PKCd and PKCe between specific intracellular compartments (Gordon et al, 1997). The subcellular redistribution of PKCe but not PKCd is also evident in cellular fractions prepared from cardiac myocytes (Miyamae et al, 1998). Moreover, acute EtOH administration differentially alters PKC expression in membrane and cytosolic fractions prepared from the rat cortex.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic EtOH exposure (48 h) promotes translocation of PKCd and PKCe between specific intracellular compartments (Gordon et al, 1997). The subcellular redistribution of PKCe but not PKCd is also evident in cellular fractions prepared from cardiac myocytes (Miyamae et al, 1998). Moreover, acute EtOH administration differentially alters PKC expression in membrane and cytosolic fractions prepared from the rat cortex.…”
Section: Discussionmentioning
confidence: 96%
“…PKC activation has been described previously in forms of preconditioning induced by ischemia or exposure to low amounts of ethanol (4,8,14). The studies in RACK-containing cardiomyocytes and transgenic mouse hearts demonstrate that even modest activation of Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Because recent studies have suggested that translocation of PKC is correlated with ischemic preconditioning in adult cardiomyocytes (8,9,14), we determined whether translocation of PKC by RACK is sufficient to confer this protection. RACK (0.5 M extracellular concentration) reduced adult cardiac myocyte damage, as assessed by osmotic fragility, after 180 min of simulated ischemia from 37 Ϯ 5 to 16 Ϯ 4%, respectively (n ϭ 3; P Ͻ 0.05) ( Fig.…”
Section: Protection Of Cardiomyocytes From Ischemia-induced Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal models, longterm alcohol consumption reduced myocardial ischemia-reperfusion injury possibly through repeated myocyte adenosine receptor activation, [119] and sustained translocation of epsilon protein kinase C (εPKC). [120] In situ studies in rabbit showed, ethanol exposure followed by washout or sufficient time to metabolize the alcohol prior to ischemia, induces preconditioning-like myocardial protection. [121] Protection afforded against ischemia and reperfusion injury (I/R) proceeds through an ischemic preconditioning-like mechanism involving the activation of εPKC that is dependent on the time and duration of ethanol treatment.…”
Section: Alcohol Preconditioningmentioning
confidence: 99%